KOMODIFIKASI PERTUKARAN PERAN GENDER PADA SINETRON DUNIA TERBALIK DI RCTI - Agus Salim; Mulharnetti Syas (Jurnal Ilmu dan Budaya, 2019)
Although the development in the field of information technology is so fast, but it doesn’t change the existence of television as a means of entertainment and information for many people in Indonesia. By being proven through the high rating of Dunia Terbalik Soap Operas and being the favorite soap opera of television viewers, it can be a benchmark for the existence of television as a means of entertainment. The high rating can instead be used as a commodification tool for television. The Dunia Terbalik Soap Opera tells about the displacement of gender roles between male and female actors, where the woman who acts as a wife has complete control over her family's economy. The theme of storytelling in Dunia Terbalik Soap Operas is rarely touched by the team worker of soap operas so that the soap opera is in demand by television viewers. This study was designed through a qualitative approach using literature studies, observations and related party interviews in the Dunia Terbalik Soap operas, researchers also sought the meaning of role exchanges in the Dunia Terbalik Soap Opera by using Semiotics Analysis so that it could find that the impact of many entertained television viewers saw an exchange of roles in The World Dunia Terbalik Soap Operas is used to bring advertisements that are part of the story in the Dunia Terbalik Soap Opera, so that proves that the soap opera becomes a political economy tool that is commodification of the contents for the Dunia Terbalik Soap Opera on RCTI.